Komodifikasi Dakwah: Analisis Fenomena Ustaz Selebriti dalam Industri Media (Pusat Riset dan Inovasi Nasional, 2024)
This study critically examines the emerging phenomenon of celebrity preachers as a significant form of religious commodification within the realm of digital da’wah. The rapid proliferation of social media has fundamentally transformed how religious messages are disseminated, with platforms like YouTube, Instagram, and TikTok becoming primary channels. Utilizing a quantitative methodology that combines comprehensive literature studies with online questionnaires distributed to social media users, this research investigates public perceptions regarding digital da’wah practices and high-profile preachers. The findings reveal a commodification process characterized by three key aspects: the tailoring of content to suit market preferences, the shift of audiences into active consumers, and the strategic construction of public images by preachers to sustain popularity. While respondents value the accessibility of digital da’wah, they strongly emphasize the necessity of ethical boundaries to preserve its spiritual essence. Consequently, digital da’wah requires sincerity, scholarly integrity, and moral responsibility to remain an authentic medium for Islamic teachings.